Sosialisasi dan Pelatihan Daur Ulang Minyak Jelantah Sebagai Sabun Cuci Piring di Desa Koto Baru - Susda Heleni; Miftahul Jannah; Dhani Radhiva Houctor Sitanggang; Muhammad Iqbal Hakim; Dea Puspita; Hamdi Fadli; Delara Ayura Salsabila; Azura Hikmah Sabrina; Fazira Fiddya Rainy (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2023)
Cooking oil is one of the ingredients that is widely used in everyday life. And if it is disposed of, it can pollute the environment. To overcome this, used cooking oil can be reused, one of which is by turning it into liquid dish soap. The purpose of carrying out this activity is to share insights with the public regarding the use of waste cooking oil into useful products. The target is PKK women in Koto Baru Village. The method used in this activity is socialization and demonstrations with PKK women. The result of this activity is that PKK Koto Baru Village women have insight into the reuse of used cooking oil waste, and are expected to be able to transfer their knowledge to the wider community. In addition, this activity can also be a business opportunity to increase income.